Health-related Quality of Life of Breast Cancer Survivors Attending an Exercise Intervention Study: A Five-year Follow-up - Roine E; Sintonen H; Kellokumpu-Lehtinen PL; Penttinen H; Utriainen M; Vehmanen L; Huovinen R; Kautiainen H; Nikander R; Blomqvist C; Saarto T (INT INST ANTICANCER RESEARCH, 2022)
Background/Aim: As the number of breast cancer survivors is increasing, their long-term health-related quality of life (HRQoL) has become an important issue. The aim of the study is to follow up the HRQoL of breast cancer survivors (BCS) in a prospective randomized exercise intervention study and to compare HRQoL to that of the age-matched general female population. Patients and Methods: Following adjuvant treatment, 537 patients aged 35-68 and capable of exercise training were randomized to a 12-month exercise trial. In 182 of those patients, HRQoL was measured by the generic 15D at baseline and followed up for five years. Furthermore, the HRQoL of all BCS answering the 15D at five-year follow-up (n=390) was compared to that of a representative sample of the general population. Results: After five years, the BCS' mean HRQoL demonstrated a statistically and clinically significant impairment compared to that of the general population (difference -0.023, p<0.001). The mean HRQoL of BCS followed up from baseline until five years did not improve significantly (change=0.007, p=0.27), whereas the dimensions of usual activities (0.043, p=0.004), depression (0.038, p=0.007), distress (0.030, p=0.036), and sexual activity (0.057, p=0.009) did. Conclusion: The HRQoL of BCS was still impaired five years following treatment.